Drug and Therapeutics (D & T) committees in Dutch hospitals: a nation-wide survey of structure, activities, and drug selection procedures - Fijn, R (Blackwell Science Inc, 1999)
AIMS: To determine structure, activities and drug selection processes used by Dutch hospital drug and therapeutics (D & T) committees. METHODS: A pretested structured survey questionnaire based on the Australian process and impact indicators, previous research, and consultation of professionals was developed. Subsequently, D & T committees that met predefined selection criteria were asked to participate. RESULTS: The overall response rate was 70% (38/54). D & T committees varied considerably in size and representation of clinical expertise. Although responsibilities were theoretically alike, actual responsibilities were frequently passed on to other authorities, such as pharmacy staff. Few committees used detailed guidelines or decision supportive matrices to establish transparency in drug selection. With respect to drug selection, the value scores on the information resources used, the factors involved, and the selection criteria used varied. Hospital pharmacists were likely to be most involved and to have the greatest impact. A consensus was most difficult to achieve for drugs used in cardiology, oncology, and psychiatry. Interference of industrial marketing strategies on drug selection was recognized and identified. CONCLUSIONS: Our results indicate that Dutch hospital D & T committees differ with respect to their clinical expertise and their activities, a situation comparable with that observed in other countries. Furthermore, the lack of transparency in drug selection was considerable. These findings clarify the differences previously found between Dutch hospital drug formularies.